2001
DOI: 10.1093/ndt/16.4.798
|View full text |Cite
|
Sign up to set email alerts
|

Changes in major blood components after adopting the supine position during haemodialysis

Abstract: This study suggests that the change from the upright to the supine positions during HD causes changes in blood components that are critical for quality control determinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…Postural changes have a profound effect on plasma volume in healthy subjects [16] and in HD patients [17]. Upon standing, the hematocrit increases because of a decrease in plasma volume due to a fluid shift from the circulation to the interstitial tissue of the dependent regions of the body.…”
Section: Problems With the Measurement Of Rbvmentioning
confidence: 99%
See 1 more Smart Citation
“…Postural changes have a profound effect on plasma volume in healthy subjects [16] and in HD patients [17]. Upon standing, the hematocrit increases because of a decrease in plasma volume due to a fluid shift from the circulation to the interstitial tissue of the dependent regions of the body.…”
Section: Problems With the Measurement Of Rbvmentioning
confidence: 99%
“…Resumption of the supine body position after standing facilitates mixing of blood between the circulatory compartments and leads to a rapid and marked temporary increase in hematocrit followed by a slow decrease [16]. Inagaki et al [17] found that hemodilution and, thus, the fluid flux from the interstitial tissue to the vascular space took more time (>30 min) in HD patients than healthy controls (<15 min). Many patients assume a supine or half-sitting position just before the start of HD (e.g.…”
Section: Problems With the Measurement Of Rbvmentioning
confidence: 99%
“…The mean UF volume was 1.51 litres and the mean UF rate was 8.1 ml/kg/h. Patients maintained a standard semi-reclining posture throughout the study [11] . Haemodynamic monitoring of BP, RBV, ECF and CO was carried out throughout the study as described below.…”
Section: Study Protocolmentioning
confidence: 99%
“…Patients were placed lying in a supine position in bed for > 20 min before the pre-dialysis sampling, and were not allowed to eat or drink until the post-dialysis sampling [11, 12]. Hematocrit (Ht), albumin (Alb), and sodium (Na) concentrations of the samples were measured.…”
Section: Methodsmentioning
confidence: 99%